Familicide: A Systematic Literature Review. (January 2021) - Karlsson, Linda C.; Antfolk, Jan; Putkonen, Hanna; Amon, Sabine; da Silva Guerreiro, João; de Vogel, Vivienne; Flynn, Sandra; Weizmann-Henelius, Ghitta
Familicides have received relatively little attention and are mostly discussed in studies with broader aims. Here, we reviewed 67 studies from 18 countries on familicides, in which an offender killed or attempted to kill their current or former spouse/intimate partner and one or more of their biological or stepchildren. We conducted a systematic literature search in PubMed, PsycINFO, and Google Scholar. Eight studies investigated familicide specifically, while the remaining reported on familicide cases as a subsample. We retrieved data on offenders' gender, age, and background as well as on victims and their relationship to the offender. We also retrieved data on contextual factors and offense characteristics (i.e., modus operandi, offense location, premeditation, and whether or not the offender had committed suicide). We also coded methodological aspects of the studies. Familicides were almost exclusively committed by men and about half of the familicide cases led to the suicide of the offender. Mental health problems, relationship problems, and financial difficulties were prevalent. Because few studies reported population base rates of the investigated characteristics, it is difficult to draw conclusions about specific risk factors. Future research should further investigate typologies of familicide and examine risk factors for different types of familicides.